The impact and role of innovative business development for economic growth - Kravec A. V. (Interactive science, 2016)
the article deals with the relationship of economic growth of the Russian economy, forming the country's new technological-sky lifestyle business with creativity, innovation and the formation of the clustering in the territory of the Russian Federation.
Keywords: экономика; креативность; потенциал; инновации; экономическая политика; экономический рост; технологический уклад; кластеры; creativity; innovation; potential; economy; Economic policy; economic growth; clusters; экономическая активность; economic activity; technological way